In vitro cultures for production of Zerumbone and mass propagation in Zingiber Zerumbet Smith / Farah Diana binti Idris - Idris, Farah Diana (2010)
Lempoyang (Zingiber zerumbet Smith.) is an important plant which has been propagated because of its medicinal values. Lempoyang is widely used as a folk medicine in Asian countries such as Malaysia, Indonesia, India and Taiwan. Zerumbone, a cyclic sesqueterpene found to be the major and main bioactive compound that gives great potential in medicinal purposes especially in the treatment of chronic diseases based on recent reports. Recently, it was found that zerumbone inhibited the growth of human leukemia cell line, HL-60 cell. Even though there are so many great values contain in the lempoyang but it is hard to obtain rhizome as raw material due to its exposure to pest and fungal infection through conventional propagation. Therefore, tissue culture was used to overcome pest and fungal infection faced through conventional propagation. In vitro plant was established in culture and acclimatized before field planting to produce rhizomes, extracted and the amount of zerumbone was compared to in vivo rhizomes. The amount was significantly higher in the in vitro derived rhizomes than in vivo rhizomes from three types of extraction methods used in this research. In addition, another promising alternative for micropropagation that could drive the efficiency of secondary metabolites production through the establishment of regenerable embryogenic cell suspension cultures. Cell suspension established in shake flask was also used as a source of zerumbone in this study. Zerumbone was found excreted in the liquid media. Even though the amount is not comparable from the in vitro derived rhizomes, but the presence can be enhanced by manipulating the production of zerumbone in future research.